Framework for Chemical Disaster Response in Vocational Education Using History Case Pedagogy - Irena Rahmawati; Anwar Kurniadi; Syamsunasir (Cita konsultindo, 2025)
Chemical disasters, whether from industrial accidents, terrorism, or armed conflict, represent complex, low-frequency but high-consequence scenarios that challenge conventional vocational disaster management education. This conceptual paper addresses the pedagogical gap in preparing disaster response personnel for chemical threats by proposing an integrated competency framework grounded in historical case analysis. Drawing on experiential learning theory, reflective practice principles, and analysis of three major chemical incidents: Halabja (1988), Tokyo (1995), and Ghouta (2013), this framework articulates a three-tiered competency structure spanning foundational awareness to incident management. The paper demonstrates how historical chemical disasters can be systematically transformed into powerful pedagogical tools that develop technical, analytical, ethical, and psychosocial competencies essential for effective crisis response. This framework contributes to vocational education scholarship by offering a replicable model for teaching rare, high-stakes scenarios and provides practical guidance for curriculum developers addressing gaps in chemical disaster preparedness education.